2022
DOI: 10.3390/rs14205174
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Low-Cost GNSS Solution for the Real-Time Deformation Monitoring of Cable Saddle Pushing: A Case Study of Guojiatuo Suspension Bridge

Abstract: Extreme loadings, a hostile environment and dangerous operation lead to the unsafe state of bridges under construction, especially large-span bridges. Global Navigation Satellite Systems (GNSS) tend to be the best choice for real-time deformation monitoring due to the significant advantage of automation, continuation, all-weather operation and high precision. Unfortunately, the traditional geodetic GNSS instrument with its high price and large volume is limited in its applications. Hence, we design and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In a few studies, low-cost GNSS receivers have been used for monitoring natural hazards [23,24], engineering structures [25][26][27][28][29], and even crustal deformation studies [30]. Notti et al [24] conducted continuous monitoring of the slope which causes deformations in the Madonna del Sasso Sanctuary in Italy using low-cost GNSS devices.…”
Section: Introductionmentioning
confidence: 99%
“…In a few studies, low-cost GNSS receivers have been used for monitoring natural hazards [23,24], engineering structures [25][26][27][28][29], and even crustal deformation studies [30]. Notti et al [24] conducted continuous monitoring of the slope which causes deformations in the Madonna del Sasso Sanctuary in Italy using low-cost GNSS devices.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of low-cost GNSS receivers in various fields, such as positioning, marine, and atmospheric studies, has been demonstrated [22][23][24]. Furthermore, recent investigation has emphasized that the deformations can be monitored with low-cost GNSS receivers [25], and they are used effectively in SHM systems [20,21,[26][27][28]. Moreover, about five years ago, u-blox, a Swiss company, released a dual-frequency GNSS receiver, the ZED-F9P, costing approximately USD 200 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Navigation system refers to the general term of all equipment combinations that can complete certain navigation and positioning tasks. At present, the main navigation systems include radio navigation system [1,2], satellite navigation system [3][4][5], astronomical navigation system [6], inertial navigation system [7,8] and integrated navigation system [9][10][11], etc.…”
Section: Introductionmentioning
confidence: 99%